Analysis of agarwood oil composition via preparative thin layer chromatography - Siti Faridah, Ab Rahman (2009)
Agarwood which is also known as Aquilaria is the most valuable wood in the world with higher prices and demands nowadays. The widely uses of agarwood in meditation field, essential oil production and etc makes agarwood one of the precious things on earth. The study was carried out to analysis compounds present in agarwood oil by using Preparative Thin Layer chromatography. In this study, used of Aquilaria Maleccencis from Malaysia as the sample and it can be classified in grade C. After extraction, isolation was carrying out to isolate it complex component present and detected by UV irradiation to afford 4 spots. Each spots, i.e spots 1, 2, 3 and 4 numbered in order of increasing polarity and each separated spot was confirmed by GC-MS. Results from GC-MS was analyzed to confirm presented of sesquiterpenes as a mojor active compound in agarwood oil and comparison between sample was made between commercial sample, i.e. Maha and Kelantan samples. This study showed a marked similar compound presented in the oil compositions among the sample and commercial samples.